In vitro Evaluation of Newer Unconventional Feedstuffs for Livestock - Banakar, Praveen S.; Kulangara, Ally; Prasad, Chikkagoudara K.; Soren, Nira M.; Dominic, George; Terhuja, Megolhubino (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The study assessed the chemical composition, digestibility, and fermentation metabolites of six unconventional feedstuffs: bambooleaves (BL), turmeric waste (TW), spent cumin (SC), cooked barley residue (CBR), water hyacinth (WH), and soya sauce waste (SSW) asruminant feedstuffs through in vitro gas production test. The crude protein content ranged from 11.82% (CBR) to 17.98% (WH), whilethe ether extract was higher in SSW, followed by TW. The neutral detergent fiber (NDF) content was lower in WH (46.6%) and higher inTW (65.83%), while the acid detergent fiber (ADF) was higher in TW and lowered in SSW. Spent cumin had higher lignin than turmericwaste. Gas production (mL/200 mg; 24 h) was higher (p
Keywords: Cooked barley residue; Digestibility; Gas production; In vitro; Spent cumin; Turmeric waste; Volatile fatty acids